PENGARUH KUALITAS PRODUK, LOKASI DAN WORD OF MOUTH (WOM) TERHADAP KEPUTUSAN PEMBELIAN DI BEBEK KALEYO BALAI PUSTAKA - Najma Fadhilah; Chatarina Yunita (LPPM Universitas Asa Indonesia, 2023)
The research analysis aims to determine the effect of product quality, location and word of mouth (WOM) on purchasing decisions at Bebek Kaleyo Balai Pustaka. The sampling collection used was purposive sampling of 100 respondents. Data collection used a questionnaire distributed to customers at Bebek Kaleyo Balai Pustaka. The population in this study were customers of Bebek Kaleyo Balai Pustaka. This research method uses quantitative methods and multiple linear regression analysis through SPSS 24. The results of this study indicate that product quality, location and word of mouth (WOM) have a positive and simultan impact on purchasing decisions at Bebek Kaleyo Balai Pustaka